A New Approach to Marriage Preparation: The Attachment-Differentiation Premarital Model. Issue 2 (3rd April 2021) - Dell'Isola, Richard; Durtschi, Jared; Topham, Glade; Gimarc, Caroline
Abstract: This article outlines a new approach to premarital intervention—the Attachment-Differentiation Premarital Model (ADPM). The ADPM was developed by drawing on existing research, clinical experience, and theoretically grounded in Bowen family systems and attachment theory. It contains seven sequential phases, each viewed as a prerequisite to the prior stage: Assessment, Empathy-Building, Communication/Conflict Management, Marital Beliefs & Values, Marital Topics, Relationship Maintenance, and Charting the Course. These phases are outlined in detail, with vignettes and special treatment considerations. Although the ADPM has a prescribed treatment plan, it is respectful of between-couple differences and thus adaptable to meet unique client/facilitator needs. Further, all ADPM materials are open access, making this model a highly accessible, practical, and theoretically-grounded option for all clinicians and facilitators.